Cinaciguat prevents the development of pathologic hypertrophy in a rat model of left ventricular pressure overload - Németh, Balázs Tamás; Mátyás, Csaba; Oláh, Attila; Lux, Árpád; Hidi, László; Ruppert, Mihály; Kellermayer, Dalma; Kökény, Gábor; Szabó, Gábor; Merkely, Béla; Radovits, Tamás (Scientific reports, 2016)
Pathologic myocardial hypertrophy develops when the heart is chronically pressure-overloaded. Elevated intracellular cGMP-levels have been reported to prevent the development of pathologic myocardial hypertrophy, therefore we investigated the effects of chronic activation of the cGMP producing enzyme, soluble guanylate cyclase by Cinaciguat in a rat model of pressure overload-induced cardiac hypertrophy. Abdominal aortic banding (AAB) was used to evoke pressure overload-induced cardiac hypertrophy in male Wistar rats. Sham operated animals served as controls. Experimental and control groups were treated with 10 mg/kg/day Cinaciguat (Cin) or placebo (Co) p.o. for six weeks, respectively. Pathologic myocardial hypertrophy was present in the AABCo group following 6 weeks of pressure overload of the heart, evidenced by increased relative heart weight, average cardiomyocyte diameter, collagen content and apoptosis. Cinaciguat did not significantly alter blood pressure, but effectively attenuated all features of pathologic myocardial hypertrophy, and normalized functional changes, such as the increase in contractility following AAB. Our results demonstrate that chronic enhancement of cGMP signalling by pharmacological activation of sGC might be a novel therapeutic approach in the prevention of pathologic myocardial hypertrophy.
Gesehen am 09.10.2020